Contribution of learning facilities and teacher professional development to teacher job satisfaction in public junior high schools - Ningsih, Sri Kurnia; Syahril, Syahril; Sabandi, Ahmad; Al Kadri, Hanif (Indonesian Research Journal in Education |IRJE|, 2026)
This study examined how learning facilities and teacher professional development contribute to job satisfaction among public junior high school teachers in Padang Pariaman Regency, Indonesia. Using a quantitative correlational design, 291 teachers were selected from a population of 1,187 through cluster sampling and proportionate stratified random sampling. Data were collected using validated, reliable Likert-scale questionnaires and analyzed using descriptive statistics, simple linear regression, and multiple linear regression in SPSS. The results indicated that learning facilities and teacher professional development each made a positive and statistically significant contribution to teacher job satisfaction. The two variables also contributed significantly to job satisfaction when examined simultaneously. These findings indicate that adequate learning facilities and sustained professional development opportunities are important organizational factors associated with teacher job satisfaction. The research emphasizes the necessity of improving school resources and providing continuous professional development to support teachers’ professional well-being.